Breast Surgery Using Thoracic Paravertebral Blockade and Sedation Alone. (20th August 2014) - Simpson, James; Ariyarathenam, Arun; Dunn, Julie; Ford, Pete
Abstract : Introduction . Thoracic paravertebral block (TPVB) provides superior analgesia for breast surgery when used in conjunction with general anesthesia (GA). Although TPVB and GA are often combined, for some patients GA is either contraindicated or undesirable. We present a series of 28 patients who received a TPVB with sedation alone for breast cancer surgery. Methods . A target controlled infusion of propofol or remifentanil was used for conscious sedation. Ultrasound guided TPVB was performed at one, two, or three thoracic levels, using up to 30 mL of local anesthetic. If required, top-up local infiltration analgesia with prilocaine 0.5% was performed by the surgeon. Results . Most patients were elderly with significant comorbidities and had TPVB injections at just one level (54%). Patient choice and anxiety about GA were indications for TVPB in 9 patients (32%). Prilocaine top-up was required in four (14%) cases and rescue opiate analgesia in six (21%). Conclusions . Based on our technique and the outcome of the 28 patients studied, TPVB with sedation and ultrasound guidance appears to be an effective and reliable form of anesthesia for breast surgery. TPVB with sedation is a useful anesthetic technique for patients in which GA is undesirable or poses an unacceptable risk.